RISIKO PEMBANGUNAN KAPAL RUMAH SAKIT DI MASA PANDEMI COVID-19 MENGGUNAKAN METODE HOUSE OF RISK - Friska Agniezka Rossalia; Fitri Hardiyanti; Yesica Novrita Devi (Proceeding Maritime Business Management Conference, 2022)
One of the shipyards of the State-Owned Enterprises (BUMN) was currently carrying out a project to build a hospital ship with a length of 124 meters. This hospital ship construction project was carried out during the COVID-19 pandemic so its implementation the physical progress of the shipbuilding project was not in accordance with the planned physical progress and the shipbuilding project was delayed. The purpose of this study to identify risks in the implementation of the hospital ship construction project during the COVID-19 pandemic. The method that can be used to handle and minimize risks in hospital shipbuildingprojects during the COVID-19 pandemic is the House of Risk (HOR) method. The results of the research on the hospital ship building project during the COVID-19 pandemic found 17 risk events and 20 risk agents. From HOR Phase 1, 11 dominant risk agents were produced with the highest Aggregrate Risk Potentials (ARP) value of 3438.5. Then in HOR Phase 2, 19 mitigation actions were obtained and from the 19 mitigation actions, 12 effective priority mitigation actions were obtained to be implemented by the company with the highest Effectiveness to Difficulty Ratio (ETD) value of 27444.05.